2020
DOI: 10.1002/slct.201904007
|View full text |Cite
|
Sign up to set email alerts
|

Cyclodextrin‐Based Nanosponges for Improving Solubility and Sustainable Release of Curcumin

Abstract: Considering the utility of cyclodextrin nanosponges for the encapsulation of drugs, in this study, the effect of drug loading method on the release property of the resulting complex is studied. To this purpose, curcumin as a model substrate was loaded into the cyclodextrin nanosponge via three different methods, including freeze drying, impregnation and physical mixing.All three complexes were characterized and the release profile of curcumin from them was investigated.[a] M. Gharakhloo, M. Rezaeetabar, Dr. A.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 51 publications
4
16
0
Order By: Relevance
“…The DSC thermogram of curcumin-loaded nanosponge compared to the plain nanosponge and curcumin is represented in Figure 5 b, and the disappearance of the curcumin endothermic peak indicates the formation of the inclusion complex and the encapsulation of curcumin inside the prepared nanosponges. Similar results were reported in the literature [ 56 , 60 ].…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The DSC thermogram of curcumin-loaded nanosponge compared to the plain nanosponge and curcumin is represented in Figure 5 b, and the disappearance of the curcumin endothermic peak indicates the formation of the inclusion complex and the encapsulation of curcumin inside the prepared nanosponges. Similar results were reported in the literature [ 56 , 60 ].…”
Section: Resultssupporting
confidence: 92%
“…The inclusion complex of curcumin with cyclodextrin polymer [ 23 , 51 , 52 , 53 , 54 ] and with cyclodextrin-based nanosponges [ 55 , 56 , 57 , 58 , 59 , 60 ] was studied thoroughly in previously published research and was reported to have an effect on the enhancement of curcumin solubility, release rate, stability, and cytotoxicity [ 55 , 56 , 57 , 58 , 59 , 60 , 61 ]. However, there was no comparison between nanosponges and direct β-cyclodextrin complexations for curcumin.…”
Section: Introductionmentioning
confidence: 99%
“…MPH and CYT were loaded in NSs using previously reported methods [ 57 ]. Briefly, 1 g of NS was dispersed in 50 mL of double-distilled water using a magnetic stirrer, and then, 20 mL each of MPH and CYT was added.…”
Section: Methodsmentioning
confidence: 99%
“…Several carrier materials have been described for liposoluble bioactive compounds, namely natural and synthetic polymers, lipid carriers and proteins, in the form of: (i) nanoand microparticles [5,94]; (ii) capsules [15]; (iii) films [149]; (iv) foams [150]; (v) hydrogels [151]; (vi) nanosponges [152]; (vii) liposomes [153] and (viii) emulsions [154]. Synthetic polymers, such as polyethylene glycol (PEG) and poly(lactic-co-glycolic) acid (PLGA) [155,156] have been described, however, the controversial safe administration of synthetic matters demonstrated the need for other biologically safe options [5].…”
Section: Challenges Of Liposoluble Compounds Deliverymentioning
confidence: 99%